2019
DOI: 10.1038/s41598-019-46499-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prognostic relevance of rectal magnetic resonance imaging findings before and after neoadjuvant chemoradiotherapy

Abstract: This retrospective study was designed to compare prognostic relevance of magnetic resonance imaging (MRI) findings before and after neoadjuvant chemoradiotherapy (CRT). From 2002 to 2010, 399 patients who underwent surgery after CRT for rectal cancer (≥T3) and had adequate pre-CRT (mr) and post-CRT (ymr) MRI findings were examined. Factors examined included tumour (T), lymph node (N), mesorectal fascia (MRF), extramural venous invasion (EMVI), and tumour regression grade (TRG). Two Cox proportional hazard mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Both found a significantly higher risk of recurrence for ymrEMVI-positive patients; Kim et al with a RR of 4.79 (95%CI 1.49-15.36, P ¼ 0.0085) 30 and Song et al with a RR of 1.93 (95%CI 1.39-2.67, P ¼ 0.0001). 37 Two other authors reported 3-year DFS rates, again showing a significantly higher recurrence risk with ymrEMVI-positive status; Chand et al with a RR of 2.70 (95%CI 1.75-4.16, P < 0.0001) 26 and Prampolini et al with a RR of 3.53 (95%CI 1.36-9.15, P ¼ 0.0095). 36 No study reported 1-year DFS rates.…”
Section: Disease Free Survivalmentioning
confidence: 92%
See 4 more Smart Citations
“…Both found a significantly higher risk of recurrence for ymrEMVI-positive patients; Kim et al with a RR of 4.79 (95%CI 1.49-15.36, P ¼ 0.0085) 30 and Song et al with a RR of 1.93 (95%CI 1.39-2.67, P ¼ 0.0001). 37 Two other authors reported 3-year DFS rates, again showing a significantly higher recurrence risk with ymrEMVI-positive status; Chand et al with a RR of 2.70 (95%CI 1.75-4.16, P < 0.0001) 26 and Prampolini et al with a RR of 3.53 (95%CI 1.36-9.15, P ¼ 0.0095). 36 No study reported 1-year DFS rates.…”
Section: Disease Free Survivalmentioning
confidence: 92%
“…39 Two other authors provided 5-year LR rates, but none of them were statistically significant for mrEMVI-positive status; Cho et al with a RR of 1.53 (95%CI 0.51-4.63, P ¼ 0.4497) 27 and Song et al with a RR of 1.62 (95%CI 0.74-3.51, P ¼ 0.2245). 37 Meng et al were the only authors to provide 3-year LR rates, but the association was not statistically significant with a RR of 1.88 (95%CI 0.12-29.19, P ¼ 0.6536). 34 No study reported 1-year LR rates.…”
Section: Local Recurrencementioning
confidence: 94%
See 3 more Smart Citations